PRINCIPLES OF SCIENTIFIC ETHICS IN THE BAD GENIUS SERIES FILM (ROLAND BARTHES SEMIONTIC ANALYSIS) - Prasety, Ella Jayahuda; Wijaya, Daya Negri (Jurusan Sastra Indonesia, 2023)
Film mass media was chosen as the most effective medium in conveying messages, because films can be used as learning media through messages that are represented in scenes or story narratives. The lessons that can be taken are in the form of moral messages, or one of them is about the moral messages of scientific ethics contained in Bad Genius. This film discusses the life of students who play with the world of education, with the vulnerabilities that are committed and get an imbalance in the form of money used to meet their needs. The type of research used is qualitative with descriptive research nature. This study uses the semiotic analysis method of Roland Barthes, in this analysis there are three core things that are the focus, namely denotative, connotative, and mythical meanings which are used as a guide to see the depiction of scientific moral messages depicted in each film scene. The data obtained in this study were sourced from the We TV application which broadcasts the Bad Genius film and was combined with books discussing films and scientific moral messages. The results of the study show that the representation of scientific moral messages shown in the Bad Genius film is how science should be used. Such as the obligation to (1) maintain an attitude in making ethical decisions related to etiquette, (2) maintain attitudes in related ethical decisions, and (3) maintain attitudes related to ethical decisions related to law. In this film, I want to highlight the side of how a student who is categorized as a genius must maintain their ethics by combining the values of education in Thailand and the values of education globally which can be used as lessons for the audience of the film Bad Genius. In addition, this film not only has a moral message of scientific ethics, but there are other moral messages related to everyday life.